Zinc, Magnesium, and Copper Levels in Patients with Sickle Cell Disease: A Systematic Review and Meta-analysis - Elkhidir, Ibrahim H.; Ali, Shahd S.; Ali, Waad K.; Madani, Hind R.; Basheir, Rawya A.; Altayeb, Rayan M.; Shazali, Rayan H. S.; Fadlelmoula, Safaa; Eltayeb, Wisal M.; Omar, Zeina I.; Elnil, Mahmoud; Mohamed, Sagad O.O. (Avicenna Journal of Medicine, 2022)
Background Sickle cell disease (SCD) is associated with oxidative stress due to an imbalance between production and elimination of the reactive oxygen species. It has been reported that SCD patients are at risk of multiple micronutrients' deficiencies, including several trace elements involved in the antioxidation mechanisms. We aimed to assess the status of these micronutrients in SCD patients.Methods This study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. The databases of MedLine, Embase, and PsycInfo were used for the systematic search from time the databases existed until April 2021. A total of 36 studies fulfilled the eligibility criteria. We calculated the pooled standardized mean difference (SMD) of serum zinc, magnesium, or copper levels among patients with SCD and their healthy controls.Results SCD patients had significantly lower zinc (SMD = −1.27 [95% CI: 1.67−0.87, p 0.001]) and magnesium levels (SMD = −0.53 [95% CI: 1.0−0.06, p 0.026] than their controls. Copper level was found to be significantly higher in SCD patients, with SMD = 0.68 (95% CI: 0.05−1.32, p 0.004).Conclusion This review showed that SCD patients may potentially prompt to have lower zinc and magnesium levels and higher copper levels compared with those without the disease. Future research need to be directed to investigate clinical outcome of nutritional difficiencies in patients with SCD, as well as the possibility of implementing nutritional supplement programs which may help minimizing the harmful effects of the disease on human body.
Keywords: sickle cell; SCD; zinc; magnesium; copper